Interaksi Investasi, Dana Pihak Ketiga dan Pembiayaan Perbankan Syariah Terhadap Pertumbuhan Ekonomi di Sumatera Utara - Sugianto Sugianto; Muhammad Yafiz; Anita Khairunnisa (ITB AAS INDONESIA Surakarta, 2021)
Economic growth is a picture to see the progress of economy a country or region, as measured with the amount of data on Gross Domestic Product (GDP) or data on Gross Regional Domestic Product (GRDP). The purpose of this study is to analyze the independence of the variables that affect economic growth, such as Domestic Investment (DI), Foreign Direct Investment (FDI), Third Party Funds (TPF) and Islamic Banking Financing. The research method uses a quantitative approach with secondary data in time series with the Vector Error Correction Model (VECM) methods and uses the help of Eviews 9 program. This study uses a sample from 2010 to 2020. The results of this study indicate that in the long run the variables of DI, FDI and Financing Islamic Banking have a positive and significant effect on the GRDP of North Sumatra, while the TPF Islamic Banking variable has a negative effect on the GRDP of North Sumatra. In the short term, the DI variable significantly affects the FDI. This study suggests that in order to advance the economy of a region, North Sumatra government should encourage and support activities carried out by DI and FDI, as well as financial institutions such as Islamic banking, which are primarily activities in the form of Third Party Funds and financing. The existence of financing disbursed by Islamic banking can provide capital assistance to business actors, so as to increase economic growth.